Local Halal Cosmetic Products Purchase Intention: Knowledge, Religiosity, Attitude, and Islamic Advertising Factors - Moh Farid Najib; Wawan Kusdiana; Izyanti Awang Razli (Journal of Islamic Economic Laws, 2022)
The demand for halal cosmetic products in various parts of the world has increased, especially in Muslim-majority countries like Indonesia. The potential demand for halal cosmetic products will continue to increase in the future. Indonesia has the opportunity to become the world's largest producer and consumer of halal cosmetic products. Therefore, Indonesia must be able to take advantage of these opportunities by maximizing its potential. This study aims to determine the effect of knowledge, religiosity, attitudes, and Islamic advertising factors on the purchase intention of local halal cosmetic products. In addition, it also aims to find out the reasons for the purchase intention of Muslim consumers towards local halal cosmetic products and to determine the purchase intentions of Muslim consumers towards imported cosmetic products in the future. This study uses 400 respondents who are Muslim and domiciled in West Java. Then to test the model and hypothesis using Smart PLS Software. The results of this study indicate that all hypotheses are accepted. Knowledge and religiosity have a positive and significant influence on attitudes and purchase intentions. Then attitude and Islamic advertising have a positive and significant influence on the purchase intention of local halal cosmetic products. Thus, in building the intention to buy local halal cosmetic products, the company must know and understand what factors underlie consumers' intentions to buy local halal cosmetic products.